ANALISIS PENGARUH BOPO, LDR, NIM, DAN GWM TERHADAP KINERJA PROFITABILITAS (ROA) DI BPD DKI JAKARTA - Wibowo, Sutrisno (JURNAL LENTERA AKUNTANSI, 2025)
This study aims to analyze the factors that affect Return on Assets (ROA) at Bank Pembangunan Daerah (BPD) Jakarta during the period 2017 from the first quarter to the fourth quarter of 2024. The method used is multiple linear regression with independent variables BOPO, Loan to Deposit Ratio (LDR), Net Interest Margin (NIM), and Minimum Required Current Account (GWM). The estimation results show that all independent variables have a significant effect on ROA at a significance level of 1%. BOPO has a negative effect on ROA, while LDR, NIM, and GWM have positive effects. Among these variables, NIM has the most dominant effect on ROA. The R-squared value of 0.9762 indicates that the model can explain 97.62% of the variation in ROA. The F test also shows that this model is significant. The Durbin-Watson value of 2.64 indicates the absence of serious autocorrelation in the data. These findings emphasize the importance of operational efficiency and interest margin management in increasing the profitability of regional banks. Thus, BPD DKI Jakarta needs to strengthen operational efficiency as well as credit distribution and fund management strategies to maintain and improve its financial performance.